EEG Microstates as a Signature of Hemispheric Lateralization in Stroke - Maria Rubega; Massimiliano Facca; Vittorio Curci; Giovanni Sparacino; Franco Molteni; Eleonora Guanziroli; Stefano Masiero; Emanuela Formaggio; Alessandra Del Felice (Brain Topography, 2024)
Stroke recovery trajectories vary substantially. The need for tracking and prognostic biomarkers in stroke is utmost for prognostic and rehabilitative goals: electroencephalography (EEG) advanced signal analysis may provide useful tools toward this aim. EEG microstates quantify changes in configuration of neuronal generators of short-lasting periods of coordinated synchronized communication within large-scale brain networks: this feature is expected to be impaired in stroke. To characterize the spatio-temporal signatures of EEG microstates in stroke survivors in the acute/subacute phase, EEG microstate analysis was performed in 51 first-ever ischemic stroke survivors [(28–82) years, 24 with right hemisphere (RH) lesion] who underwent a resting-state EEG recording in the acute and subacute phase (from 48 h up to 42 days after the event). Microstates were characterized based on 4 parameters: global explained variance (GEV), mean duration, occurrences per second, and percentage of coverage. Wilcoxon Rank Sum tests were performed to compare features of each microstate across the two groups [i.e., left hemisphere (LH) and right hemisphere (RH) stroke survivors]. The canonical microstate map D, characterized by a mostly frontal topography, displayed greater GEV, occurrence per second, and percentage of coverage in LH than in RH stroke survivors (p < 0.05). The EEG microstate map B, with a left-frontal to right-posterior topography, and F, with an occipital-to-frontal topography, exhibited a greater GEV in RH than in LH stroke survivors (p = 0.015). EEG microstates identified specific topographic maps which characterize stroke survivors’ lesioned hemisphere in the acute and early subacute phase. Microstate features offer an additional tool to identify different neural reorganization.

Assessment of Event-Related EEG Power After Single-Pulse TMS in Unresponsive Wakefulness Syndrome and Minimally Conscious State Patients - Emanuela Formaggio; Marianna Cavinato; Silvia Francesca Storti; Paolo Tonin; Francesco Piccione; Paolo Manganotti (Brain Topography, 2016)

Coherence and Consciousness: Study of Fronto-Parietal Gamma Synchrony in Patients with Disorders of Consciousness - Marianna Cavinato; Clara Genna; Paolo Manganotti; Emanuela Formaggio; Silvia Francesca Storti; Stefania Campostrini; Chiara Arcaro; Emanuela Casanova; Valeria Petrone; Roberto Piperno; Francesco Piccione (Brain Topography, 2015)

Time–Frequency Modulation of ERD and EEG Coherence in Robot-Assisted Hand Performance - Emanuela Formaggio; Silvia Francesca Storti; Ilaria Boscolo Galazzo; Marialuisa Gandolfi; Christian Geroin; Nicola Smania; Antonio Fiaschi; Paolo Manganotti (Brain Topography, 2015)

Wavelet Analysis as a Tool for Investigating Movement-Related Cortical Oscillations in EEG-fMRI Coregistration - Silvia Francesca Storti; Emanuela Formaggio; Alberto Beltramello; Antonio Fiaschi; Paolo Manganotti (Brain Topography, 2010)

EEG and fMRI Coregistration to Investigate the Cortical Oscillatory Activities During Finger Movement - Emanuela Formaggio; Silvia Francesca Storti; Mirko Avesani; Roberto Cerini; Franco Milanese; Anna Gasparini; Michele Acler; Roberto Pozzi Mucelli; Antonio Fiaschi; Paolo Manganotti (Brain Topography, 2008)

Corticospinal excitability in human subjects during nonrapid eye movement sleep: single and paired-pulse transcranial magnetic stimulation study - Mirko Avesani; Emanuela Formaggio; Giorgio Fuggetta; Antonio Fiaschi; Paolo Manganotti (Experimental Brain Research, 2008)